Aspectos emocionais e concepções de maternidade de mulheres inférteis em programa de reprodução assistida - Marciano, Rafaela Paula (2022)
Introduction: According to the WHO, infertility affects around 48 million couples worldwide.  The reproductive technology provide a privileged field in possible harmonization between the feminine and the desire of having a child.  Consider social and psychological importance of motherhood and reproduction in our society, infertility can affect the emotional, sexual and marital relationship spheres. Objectives: To understand the conceptions of motherhood and to analyze the emotional aspects of infertile women of different socioeconomic levels who are undergoing assisted reproduction treatment. Methodology: Descriptive, quali-quantitative study carried out between January and December 2019, in a private clinic and in a public clinic for assisted reproduction, both located in the city of Goiânia, Goiás. The study included 48 women, over 35 years old, undergoing treatment for high-complexity assisted reproduction, half of the sample from each institution. Individual interviews were conducted, which were recorded and transcribed in full. Results: The average age of the participants was 38.9 years, 43.75% of the sample was nulliparous, 56.2% had a female cause of sterility. The variables which had significant statistic difference were the schooling (p=0,005) and family income (p=<0,001). The women from the private clinic have shown higher schooling anda familiar income than from the public one. The participants represented the family in positive way, as a support system, of foundation and origin of love, embracing the family as a social bond. On the other hand the family concepts based on inbreeding were also present representing the family by perpetuation of the specie and by the importance of biological bond. Infertile women reported feelings of inferiority, worthlessness, impotence, inadequacy towards society, which reinforces the stigma of infertility. The prevalent feelings and symptoms were anxiety, anguish, insomnia, binge eating, sadness, frustration, fear and anger.  Infertility was represented with negative feelings related to pain, surprise and bitterness, in addition to anger, revolt and indignation, experiencing this situation as injustice against them or as a divine punishment. Conclusions: The results found contribute to necessary reflections on the role of women and our culture, since motherhood is still used as a measure for female success or failure. The woman experiences a dilemma between her desires, her reality and the possibility of choosing motherhood, but the latter is veiledly imperative. In addition, it is possible to raise the discussion on the issue of desire and demand for a biological child, aspects often forgotten in assisted reproduction clinics. At the same time, the possibility of procreation through RT is recognized as something positive for women who have the legitimate desire for biological motherhood and who find in science a possible ally to overcome the mark that their own body imposes on them.